2001
DOI: 10.1108/09513540110366097
|View full text |Cite
|
Sign up to set email alerts
|

Business students’ perceptions of faculty evaluations

Abstract: Students are asked to evaluate faculty on a continual basis at most universities throughout the world, yet students have varying perceptions about the purpose and usefulness of these evaluations. While research has focused on the faculty issues regarding evaluations and their use in subsequent evaluation, yearly reviews, tenure decisions, and even post‐tenure review, little research has been conducted to evaluate student feelings on the evaluations. In a case study format, a random sample of College of Busines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…For example, instructors who are perceived as warm, kind, funny, enthusiastic or entertaining may receive higher student ratings, regardless of their level of knowledge in the subject being taught (e.g. Ahmadi, Helms, and Raiszadeh 2001;Feldman 1986;Widmeyer and Loy 1988;Wilson 1998). Warm interpersonal style, personal charisma, self-assurance and professionalism in teaching approach have been indicated as important qualities of an ideal instructor (Bennett 1982).…”
Section: Instructor Personality and Setsmentioning
confidence: 97%
“…For example, instructors who are perceived as warm, kind, funny, enthusiastic or entertaining may receive higher student ratings, regardless of their level of knowledge in the subject being taught (e.g. Ahmadi, Helms, and Raiszadeh 2001;Feldman 1986;Widmeyer and Loy 1988;Wilson 1998). Warm interpersonal style, personal charisma, self-assurance and professionalism in teaching approach have been indicated as important qualities of an ideal instructor (Bennett 1982).…”
Section: Instructor Personality and Setsmentioning
confidence: 97%
“…Another area of investigation with regard to student evaluations of teaching is student perceptions of the evaluation process, although some authors have commented that student attitudes have received little research attention (Ahmadi, Helms, & Raiszadeh, 2001; Dommeyer, Baum, & Hanna, 2002). Abbott, Wulff, Nyquist, Ropp and Hess (1990) argue that this line of research is important because “student satisfaction may affect students' willingness to participate, may influence their opinions about teaching effectiveness, or both” (Discussion section, p. 1).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hobson and Talbot, 2001; Cooladarci, T. & Kornfield, 2007 and references contained therein) reviewed research on the reliability and validity of student evaluations and concluded that "well-developed student evaluations with adequate reliability and validity data may provide some of the best measures of teaching effectiveness." In spite of this research, it is not uncommon to find students who doubt value of these university administered evaluations (Ahmadi et al, 2001). Similarly, many faculty doubt the ability of these instruments to measure their teaching.…”
Section: Results From Previous Studymentioning
confidence: 99%